2007
DOI: 10.1111/j.1365-4632.2007.03265.x
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic response of fungal granuloma following facial herpes zoster infections – report of three cases

Abstract: Localized isotopic fungal infections, although rare, can occur in immunocompetent patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 19 publications
(40 reference statements)
1
19
0
1
Order By: Relevance
“…Diverse ‘isotopic’ responses at healed HZ sites include: vitiligo [566], fungal granuloma [567], furuncles [568], granulomatous reactions [569–574], erythemas [575–578], lichen planus [579, 580], morphea and bullae [581583], perforating collagenosis [584, 585], keratolysis [586] and sarcoidosis [587, 588], reticulohystiocytosis [589], nodular degeneration [590, 591], verrucous hyperplasia [592], mucinosis [593], urticaria [594], prurigo nodularis [595], graft-versus-host reaction [596], drug-induced eruption [597], adenocarcinoma [598], leukaemia cutis [599], Kaposi’s sarcoma [600], and tufted angioma [601]. …”
Section: Complicating Presentations and Disease Associationsmentioning
confidence: 99%
“…Diverse ‘isotopic’ responses at healed HZ sites include: vitiligo [566], fungal granuloma [567], furuncles [568], granulomatous reactions [569–574], erythemas [575–578], lichen planus [579, 580], morphea and bullae [581583], perforating collagenosis [584, 585], keratolysis [586] and sarcoidosis [587, 588], reticulohystiocytosis [589], nodular degeneration [590, 591], verrucous hyperplasia [592], mucinosis [593], urticaria [594], prurigo nodularis [595], graft-versus-host reaction [596], drug-induced eruption [597], adenocarcinoma [598], leukaemia cutis [599], Kaposi’s sarcoma [600], and tufted angioma [601]. …”
Section: Complicating Presentations and Disease Associationsmentioning
confidence: 99%
“…İzotopik yanıtta, sıklıkla granülomatoz reaksiyonlar meydana gelmektedir. Granülomatoz reaksiyonun en sık olarak meydana gelmesinin nedeni tam olarak bilinmemektedir (6). Ancak bazı kaynaklarda; herpes zoster sonrasında varisella zoster virüsteki (VZV) zarf glikoproteininin yıkımı neticesinde gecikmiş tipte hipersensitivite reaksiyonu olduğu, bunun da granülomatoz reaksiyona neden olabileceği ileri sürülmektedir (7).…”
Section: Olguunclassified
“…[1416] It has also been suggested that, tumor necrosis factor-α may have a role in the Wolf isotopic response as it is an important mediator in a variety of inflammatory and granulomatous diseases. [22]…”
Section: Pathogenesis Of Isotopic Responsementioning
confidence: 99%
“…In addition we review the cases that have been reported in the past decade [Table 1]. [2345678910111213141516171819202122232425262728293031323334353637383940414243444546474849505152] We also examine the related phenomenon like reverse isotopic response and isoradiotopic response.…”
Section: Introductionmentioning
confidence: 99%